Programa um milhão de cisternas rurais (P1MC): mudanças no acesso à água no município de Porteirinha/MG - Nascimento, Maria Pereira (2016)
Currently, public policies destined for the Brazilian semiarid region concentrate on the perspective that it is possible to live with drought. The formulation and implementation of the P1MC is an initiative of civil society in cooperation with the federal government, aiming at the creation of water reservoirs for facing the periods of drought in the semiarid region. The evaluation is little practiced in public policies, which, in general, come to an end during the implementation process. However, the investigation of this research presents evaluative character. It is during the evaluation process that it is possible to identify what went wrong and promote the due adjustments. This work concentrated in the construction and development of a research regarding the investigation of changes that occurred concerning water access after the implementation of the P1MC in the municipality of Porteirinha, Minas Gerais, Brazil. Thus, the intent was to seek an answer to the following question: which changes occurred in water access after the implementation of the P1MC in the municipality of Porteirinha/MG? The general objective was to analyze the social changes that occurred in water access after the implementation of the P1MC in the municipality of Porteirinha/MG. Therefore, the effort was directed to the development and fulfilment of the following specific objectives: a) describe the P1MC program, its actors and institutions in relation to water access; b) identify the reality of the families regarding the organization of water access after the P1MC; c) analyze the lifestyle of the families regarding water access after the P1MC; d) relate the chances occurred in relation to water access of the families benefited by the implementation of the P1MC. In fulfilling these objectives, a qualitative research was conducted, using interview as data collection method, and a semi-structured script to subsidize this collection. The interviews were recorded and notes taken, which allowed the information survey to meet the listed objectives. Data analysis was conducted by means of critical discourse analysis, considering the content and the non-verbal aspects of the interview. The field results showed that the P1MC reached the proposed objective of allowing water access during the drought period.